Development of an Educational Curriculum for Spinal Cord Stimulation. Issue 5 (13th April 2020) - Abd‐Elsayed, Alaa; Abdallah, Rany; Falowski, Steven; Chaiban, Gassan; Burkey, Adam; Slavin, Konstantin; Guirguis, Maged; Raslan, Ahmed M.
Abstract : Background: Spinal cord stimulators (SCSs) are used for treating chronic pain. The number of SCSs implanted each year is on the increase. The North American Neuromodulation Society (NANS) education committee aimed to develop a SCS curriculum as a tool to guide physicians at different training levels, based on the most recent evidence. Material and Methods: A multidisciplinary (anesthesiology, physical medicine, neurosurgery, and neurology), taskforce representing the education committee of the NANS met to develop a SCS curriculum following the Accreditation Council for Graduate Medical Education (ACGME) milestones. The task force used the best available evidence and knowledge to develop the curriculum. Once developed, the SCS curriculum was then approved by the NANS board. Results: The task force developed a SCS training curriculum. Milestones included patient care and procedural skills, system‐based practice, medical knowledge, interpersonal communication, practice based learning and professionalism. Each milestone was defined for three categories, early learner, advanced learner, and practitioner. Conclusion: A multidisciplinary task force of the NANS education committee developed a SCS training curriculum that defines ACGME milestones for basic learners, advanced learners, and practitioners.